Impacts of aggregate geometrical features on the rheological properties of asphalt mixtures during compaction and service stage. (15th November 2016) - Pei, Jianzhong; Bi, Yanqiu; Zhang, Jiupeng; Li, Rui; Liu, Guozhu
Highlights: Sieving diameter, shape index and angularity of aggregate were characterized. SGC indexes were used to study the compactability of asphalt mixture. Creep slope and E ∗ were used to study in-service rheological properties. Gray relational analysis method was applied. Relation between mixture properties and geometrical features were studied. Abstract: To study the influence of aggregates geometrical features on the rheological properties of asphalt mixtures during compaction and service stage, asphalt mixtures with partially substituted aggregates were compacted by Superpave gyratory compaction (SGC), and their properties in service were measured by creep and dynamical modulus tests. The relation between rheological properties of mixtures and aggregate geometrical features was studied by gray relational analysis method. Results show that the rheological properties of mixtures during compaction and service stage are more sensitive to sieving diameter and shape index, but are less sensitive to angularity. The results indicate potential for using these parameters for quality control and quality assurance of asphalt mixture during production.